Photosynthetic Properties and Potentials for Improvement of Photosynthesis in Pale Green Leaf Rice under High Light Conditions - Gu, Junfei; Zhou, Zhenxiang; Li, Zhikang; Chen, Ying; Wang, Zhiqin; Zhang, Hao; Yang, Jianchang (Frontiers in Plant Science, 2017)
Light is the driving force of plant growth, providing the energy required for photosynthesis. However, photosynthesis is also vulnerable to light-induced damage caused by the production of reactive oxygen species (ROS) in the PSII reaction center. Plants have therefore evolved various protective mechanisms such as non-photochemical quenching (NPQ) to dissipate excessively absorbed solar energy as heat; however, photoinhibition and NPQ represent a significant loss in solar energy and photosynthetic efficiency, which lowers the yield potential in crops. To optimize light capture and light energy conversion in rice, a genotype with pale green leaves (pgl) and a normally pigmented control (Z802) were subjected to high (HL) and low light (LL). Chlorophyll content, light absorption, chloroplast micrographs, abundance of light-harvesting complex (LHC) binding proteins, electron transport rates (ETR), photochemical and non-photochemical quenching, and generation of reactive oxygen species (ROS) were subsequently examined. Pgl had a smaller size of light-harvesting chlorophyll antenna and absorbed less photons than Z802. NPQ and the generation of ROS were also low, while photosystem II efficiency and ETR were high, resulting in improved photosynthesis and less photoinhibition in pgl than Z802. Chlorophyll synthesis and solar conversion efficiency were higher in pgl under HL compared to LL treatment, while Z802 showed an opposite trend due to the high level of photoinhibition under HL. In Z802, excessive absorption of solar energy not only increased the generation of ROS and NPQ, but also exacerbated the effects of increases in temperature, causing midday depression in photosynthesis. These results suggest that photosynthesis and yield potential in rice could be enhanced by truncated light-harvesting chlorophyll antenna size.